2015
DOI: 10.14573/altex.1510051
|View full text |Cite
|
Sign up to set email alerts
|

Non-animal models of epithelial barriers (skin, intestine and lung) in research, industrial applications and regulatory toxicology

Abstract: SummaryModels of the outer epithelia of the human body -namely the skin, the intestine and the lung -have found valid applications in both research and industrial settings as attractive alternatives to animal testing. A variety of approaches to model these barriers are currently employed in such fields, ranging from the utilization of ex vivo tissue to reconstructed in vitro models, and further to chip-based technologies, synthetic membrane systems and, of increasing current interest, in silico modeling approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 470 publications
(450 reference statements)
1
103
0
Order By: Relevance
“…They also found toxic sequence in kidney cell line in this experiment [30]. Gordon et al recently researched non-animal models of epithelial barriers (skin, kidney, intestine and lung) in research, industrial applications and found regulatory toxicology dilemma in these vital organs in histological and gross view [31].…”
Section: Nephrotoxicity From Histological Point Of Viewsupporting
confidence: 53%
“…They also found toxic sequence in kidney cell line in this experiment [30]. Gordon et al recently researched non-animal models of epithelial barriers (skin, kidney, intestine and lung) in research, industrial applications and found regulatory toxicology dilemma in these vital organs in histological and gross view [31].…”
Section: Nephrotoxicity From Histological Point Of Viewsupporting
confidence: 53%
“…CAAT has started a number of collaborative programs to advance safety sciences, which include the Human Toxome Collaboration (see above), the Evidence-based Toxicology Collaboration (see below), the Good Cell Culture Practice Collaboration (Pamies et al, 2017) building on earlier work steered by ECVAM (Coecke et al, 2005), the Good ReadAcross Practice Collaboration (Patlewicz et al, 2014, Ball et al, 2016Zhu et al, 2016), the Refinement Collaboration (Zurlo and Hutchinson, 2014) and others. CAAT's transatlantic think tank for toxicology (t 4 ) has organized more than 30 workshops to advance concepts of toxicology such as integrated testing strategies (Hartung et al, 2013b;Rovida et al, 2015b), epithelial barrier models (Gordon et al, 2015), 3D cell cultures (Alépée et al, 2014), microphysiological systems (Marx et al, 2016), high-content imaging (van Vliet et al, 2014), and has commissioned a number of white papers. (Andersen et al, 2011.…”
Section: Strategic Planning In Toxicologymentioning
confidence: 99%
“…We can analyze the kinetics of substances in different species, including man, and improve our extrapolation to humans (Bale et al, 2014;Tsaioun et al, 2016), especially by integrating information from in vitro epithelial barrier models (Gordon et al, 2015). We can use and properly report the right statistics, which in turn will strongly increase the necessary animal group sizes.…”
Section: Discussionmentioning
confidence: 99%